Restoration of motility to an Escherichia coli fliA flagellar mutant by a Bacillus subtilis sigma factor. - Chen, Y F (1992)
The activation of additional promoter sites by production of an alternative sigma subunit for RNA polymerase is a common strategy for the coordinate regulation of gene expression. Many alternative sigma factors control genes for specialized, and often narrowly distributed, functions. For example, most of the alternative sigma factors in Bacillus subtilis control genes necessary for endospore formation. In contrast, the B. subtilis sigma D protein controls the expression of genes important for flagellar-based motility and chemotaxis, a form of locomotion very broadly distributed in the eubacteria. A homologous sigma factor, sigma F, controls a similar group of motility genes in the enteric bacteria. The conservation of both promoter specificity and genetic function in these two regulons allowed us to test the ability of a B. subtilis sigma factor to function within an Escherichia coli host. We demonstrate that expression of the B. subtilis sigD gene restores motility to an E. coli strain mutant in the fliA locus encoding the sigma F factor. This result suggests that the B. subtilis sigma D protein can bind to the E. coli core RNA polymerase to direct transcription initiation from at least four of the late operon promoters, thereby leading to the synthesis of flagellin, motor, and hook-associated proteins. Conversely, expression of sigma D protein in a normally chemotactic strain of E. coli (fliA+) leads to a hyperflagellated, nonchemotactic phenotype.